IMPLEMENTASI PEMBELAJARAN TAFSIR AHKAM MELALUI LAGU QUR-ANY DI PONDOK PESANTREN AL URWATUL WUTSQO BULUREJO DIWEK JOMBANG - Maratul Azizah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
This study discusses the Implementation of Tafsir Ahkam subject through Qur-any song at Al Urwatul Wutsqo Islamic Boarding School Bulurejo Diwek Jombang which focused on finding out the Planning, Implementation and Evaluation it. The results of the study found that the planning of learning Tafsir Ahkam through Qur-any song are: formulating objectives, determining material, methods and media as supporting teaching and learning activities. Then, the teachers invited the students to read the surah al-fatihah. After that they read short praying and sholawat Ghofur before the teachers come. The implementation of Tafsir Ahkam through the Qur-any song are listening carefully, they were then invited to sound together, and practicing together. The evaluation was done by asking students to memorize, then writing what they have memorized.